2017
DOI: 10.1002/acm2.12195
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time intrafraction prostate motion during linac based stereotactic radiotherapy with rectal displacement

Abstract: BackgroundKilovoltage Intrafraction Monitoring (KIM) is a method which determines the three‐dimensional position of the prostate from two‐dimensional kilovoltage (kV) projections taken during linac based radiotherapy treatment with real‐time feedback. Rectal displacement devices (RDDs) allow for improved rectal dosimetry during prostate cancer treatment. This study used KIM to perform a preliminary investigation of prostate intrafraction motion observed in patients with an RDD in place.MethodsTen patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Larger required margins have been reported as well, up to 4.4 mm SI and 5.2 mm AP based on pre-and post-treatment imaging during SBRT (25), and 5.4 mm (SI) and 5.0 mm (AP) based on Calypso data during conventional fractionation (27). Notably, some studies have noted translations as small as 0.01 ± 0.23 mm (LR), 0.11 ± 0.64 mm (AP), and 0.21 mm ± 0.12 (SI) with incorporation of a rectal distension device and realtime kV infraction monitoring (20). A strength of the present study, however, is the large patient cohort, as the majority of prior published studies have included fewer than 100 patients, and many with fewer than 50 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger required margins have been reported as well, up to 4.4 mm SI and 5.2 mm AP based on pre-and post-treatment imaging during SBRT (25), and 5.4 mm (SI) and 5.0 mm (AP) based on Calypso data during conventional fractionation (27). Notably, some studies have noted translations as small as 0.01 ± 0.23 mm (LR), 0.11 ± 0.64 mm (AP), and 0.21 mm ± 0.12 (SI) with incorporation of a rectal distension device and realtime kV infraction monitoring (20). A strength of the present study, however, is the large patient cohort, as the majority of prior published studies have included fewer than 100 patients, and many with fewer than 50 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Variables affecting intra-fractional target motion include bladder and rectal filling, treatment time, target size, and tissue density (15)(16)(17)(18). Rectal and bladder filling are generally the greatest contributors to prostate displacement, and as a result, prostate displacement tends to be greatest in the superior-inferior (SI) and anterior-posterior (AP) directions (9,(17)(18)(19)(20). Motions can be transient, such as those created by movement of gas through the rectum, or sustained, such as continuous filling of the bladder and rectum (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This motion can cause the target to be missed or disruption of dose distribution. Legge et al 12 demonstrated with kilovoltage intrafraction monitoring that the intrafraction motion of the prostate is greater than 3 mm only in 0.4% of cases. Curtis et al evaluated necessary PTV margins according to the frequency of image acquisition.…”
Section: Intrafraction Motionmentioning
confidence: 99%
“…Also, studies have been investigated the impact of a RR on the intrafraction prostate motion during VMAT using cone‐beam CT (CBCT) and kilovoltage intrafraction monitoring (KIM). As demonstrated in these studies, intrafraction prostate motion was reduced by a RR . Thus, advantages in terms of low cost, rectal dose sparing, reproducibility of the rectal wall position, and prostate stabilization can be achieved with RR.…”
Section: Discussionmentioning
confidence: 61%